An Experimental Study and Analysis of the Mechanical Properties of Titanium Dioxide Reinforced Aluminum (AA 5051) Composite. (2018) - Lata, Surabhi; Pandey, Ankur; Labhansh,; Sharma, Ankit; Meena, Kuldeep; Rana, Ramakant; Lal, Roop
Abstract: The research work investigates the mechanical properties of aluminium reinforced with titanium dioxide particles which is fabricated through casting process. A comparative study has been conducted by varying the percentage of the reinforcement in the base metal matrix. The composite was casted and the samples were prepared, by simple turning and milling processes, for performing various mechanical tests. The reinforcement i.e. titanium dioxide weight percent of 5%, 10% and 15% resulted in increasing ultimate tensile strength, impact strength, average hardness and density with increasing concentration of titanium dioxide particles, while the compressive strength decreases with increase in the concentration of titanium dioxide reinforcement. Hence, it can be concluded that as the percentage of titanium dioxide increases the properties show enhancement due to the development of strong bonding between the particles of reinforcement and the base matrix and also due to the wettability property of the reinforcement in the base metal matrix.